Estimation of malondialdehyde levels in serum and saliva of children affected with sickle cell anemia - Sudhindra Baliga; Minal Chaudhary; Sham Bhat; Pooja Bhansali; Akshat Agrawal; Satwik Gundawar (Wolters Kluwer Medknow Publications, 2018)
Background: Sickle cell anemia (SCA) is an inherited disorder of hemoglobin synthesis characterized by deformed erythrocytes. Hemoglobin S present in sickle-shaped erythrocytes exhibits an enhanced rate of auto-oxidation compared with normal hemoglobin A. It produces more of reactive oxygen species (ROS) which promotes oxidatively stressed environment. ROS degrade the membranes of sickle cell erythrocytes composed of polyunsaturated lipids and form malondialdehyde (MDA) as a by-product. Aim: The aim of the study is to evaluate and compare the MDA levels of serum and saliva in SCA patients. Design: A total of 150 children aged 4-12 years were divided into two groups: Group A (n = 75) consisting of children suffering from SCA and Group B (n = 75) consisting of healthy children. Blood and saliva samples were collected aseptically from both the groups, and they were subjected to thiobarbituric acid assay. Absorbance was evaluated spectrophotometrically at 531 nm, and the values of concentration of MDA were derived. Results: The mean MDA levels in serum and saliva were 8.9825 ± 1.04 and 0.5152 ± 0.28, respectively, in Group A and they were found to be higher than mean MDA levels of serum (5.87 ± 0.92) and saliva (0.2929 ± 0.06) of Group B and the difference of their mean was found to be statistically significant. Conclusion: A significant correlation of the MDA was found in saliva and serum of the patients with SCA. This finding suggests that saliva can be effectively used as a noninvasive alternative for assessing the oxidative stress in patients with SCA.